Pengukuran Efektivitas Sistem Pelayanan Perizinan Berusaha Online Single Submission di Dinas Penanaman Modal dan Perizinan Terpadu Kabupaten Garut - Qorina Dzulfi Rizkiani; Sudjana (Indonesian Accounting Research Journal, 2022)
This study aimed to determine the effectiveness of the OSS system implemented at the Integrated Licensing and Investment Office of Garut Regency using five variables from the Delone & McLean Model system success theory, namely system quality, information quality, service quality, user satisfaction, and net benefits. This study employed the quantitative approach. A simple random sampling technique was used to choose the sample in this study, which consisted of 100 OSS system users. The source of research data was primary data derived from questionnaires. Data analysis was performed using the Partial Least Square (PLS) method using SmartPLS 3.3.9 software. The results revealed that the quality of information and service quality proved to have a positive and significant effect on user satisfaction, while the quality of the system was not proven to have an effect on user satisfaction. The variable of user satisfaction was then shown to have a positive and significant impact on net benefits.